Structural, mechanical and electrical properties biopolymer blend nanocomposites derived from poly (vinyl alcohol)/cashew gum/magnetite. (12th January 2018) - Ramesan, M T; Jayakrishnan, P; Manojkumar, T K; Mathew, G
Abstract: Blending of poly vinyl alcohol (PVA) and natural biopolymers such as cashew gum (CG) with magnetite (Fe3 O4 ) nanoparticles has been a promising way for preparing bio-degradable polymeric blend nanocomposites. PVA/CG/Fe3 O4 blend nanocomposites have been prepared by a simple solution casting technique using water as the green solvent. The characterization of blend nanocomposites has been carried out by using Fourier transform infrared, UV, x-ray diffraction (XRD), high resolution transmission electron microscopy, scanning electron microscopy (SEM), differential scanning calorimetry, thermogravimetric analysis, mechanical properties and electrical conductivity. The interaction between nanoparticles and the blend segments was confirmed from the shift in characteristic absorption peaks of nanocomposites compared to PVA/CG blend. XRD analysis has shown the presence of crystalline peaks of nanoparticles in the blend matrix. The uniform distribution of Fe3 O4 nanoparticles in the blend was revealed by TEM and SEM. The strong interaction of nanoparticles with the blend has been confirmed by the increase in glass transition temperature resulting from the reduced flexibility of the blend nanocomposite compared to that of the blend system. An increase in thermal stability and tensile strength and reduction in elongation at break of nanocomposites have been noticed with the increasing loading of nanoparticles. The AC electrical conductivity, dielectric constant and dielectric loss of the nanocomposites have been found to be higher than that of the blend. Generally, it can be stated that the magnetite nanoparticles acts as a potential filler in the PVA/CG blend at 7 wt% loading, giving the best balance of properties.